PROGRESS REPORT APPLICATION FOR CHILDREN WITH SPECIAL NEEDS - Sim, Yee Ming (Universiti Malaysia Sarawak (UNIMAS), 2020)
Document management is crucial for a childcare centre to keep the child information record. The current process of information record-keeping is filling paper forms and store it in files with different labelling for easy retrieval. However, more and more problems will arise as the record grows, and it will take more time for record retrieval as there are more labelling inside a file cabinet. The purpose of this project is to develop a Progress Report Application for Children with Special Needs for Pertubuhan PDK Sentuhan Kasih. Currently, the childcare centre does not have a digital application to manage child information. This proposed application provides the childcare centre to store data and provide a platform for the parent to view the child progress report. To achieve the project objectives, Madam Norhayati, one of the members of the EIP team of the Pertubuhan PDK Sentuhan Kasih has explained her needs and demonstrated the management flow of the care centre. The methodology to be used for this project is Rapid Application Development Model. The application is design after analysing three existing application in the market. The applications are Childcare Management Software for Early Education by ECCESoft (Cirrutech, 2014), Daily Connect by Seacloud Software (Seacloud, n.d) and Bloomz by Bloomz (Bloomz, 2017).